Ecological Assessment of Some Species of Medicinal Plants in the Republic of Karakalpakstan - Shaniyazov Shakhimardan Olzhabaevich, Mambetullaeva Svetlana Mirzamuratovna, Tursunboyev Hamdam Yeshboevich (Drugs and Cell Therapies in Hematology, 2021)
The article presents the results of a study on the environmental assessment of some types of medicinal plants on the territory of the Republic of Karakalpakstan. The new results obtained on the ecological assessment of some types of medicinal plants in the new ecological conditions of the Republic of Karakalpakstan will help to rationally use different groups of medicinal plants.